SLEEP DISORDERS IN CHILDREN WITH CEREBRAL PALSY: SYSTEMATIC REVIEW. (Fiep Bulletin - online, 2016)
Introduction: An adequate night of sleep is basic for the motor and cognitive development. Recent studies report that children with Cerebral Palsy (CP) have a greater risk for developing sleep disorders (SD) with predominance of obstructive sleep apnea syndrome, difficulty to fall sleep and difficulty to stay asleep and sleep-disordered breathing. The CP is actually a group of disorders in the development of the motor and postural control which emerges from a non-progressive damage in the development of the central nervous system and it may be related to cognitive deficit. Objective: To organize scientific evidences related with sleep disorders in children with cerebral palsy. Method: searches in the databases Scielo, Pubmed/Medline, Lilacs and PEDro, using the word-keys: “sleep disorders”, combined with “children” and “cerebral palsy". Studies published in the last 10 years in Portuguese, English or Spanish and that related SD and CP had been considered. Review studies or those that didn't directly approach sleep disorders related to cerebral palsy had been excluded. The articles were completely analyzed by means of a structuralized script. Results: 65 articles were initially identified, but only 6 were adequate for the inclusion criteria. Amongst them, three had the higher incidence of sleep disorders in children with cerebral palsy and three showed lesser quality of life in the group with cerebral palsy. CONCLUSION Although it is known that SD are common in children with CP, few studies exist that explore these problems in this specific population.
Keywords: sleep disorders; children; cerebral palsy.